2007
DOI: 10.1029/2006jd007995
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trend analysis of aerosol variables at the high‐alpine site Jungfraujoch

Abstract: [1] This study reports the first long-term trend analysis of aerosol optical measurements at the high-alpine site Jungfraujoch, which started 10.5 years ago. Since the aerosol variables are approximately lognormally distributed, the seasonal Kendall test and Sen's slope estimator were applied as nonparametric methods to detect the long-term trends for each month. The yearly trend was estimated by a least-mean-square fit, and the number of years necessary to detect this trend was calculated. The most significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 38 publications
3
84
2
3
Order By: Relevance
“…The Jungfraujoch (JFJ) measurement site is a Global Atmosphere Watch (GAW) station where different aerosol properties have been continuously measured since 1995 (Nyeki et al, 1998;Collaud Coen et al, 2007). The site is situated in the Bernese Alps in Switzerland at 3580 m a.s.l.…”
Section: Methodsmentioning
confidence: 99%
“…The Jungfraujoch (JFJ) measurement site is a Global Atmosphere Watch (GAW) station where different aerosol properties have been continuously measured since 1995 (Nyeki et al, 1998;Collaud Coen et al, 2007). The site is situated in the Bernese Alps in Switzerland at 3580 m a.s.l.…”
Section: Methodsmentioning
confidence: 99%
“…Mertes et al, 2007;Verheggen et al, 2007;Cozic et al, 2008;Targino et al, 2009;Kamphus et al, 2010;Zieger et al, 2012). The aerosol measurements performed at the JFJ are part of the Global Atmosphere Watch (GAW) program of the World Meteorological Organization since 1995 (Collaud Coen et al, 2007). Long term studies have been conducted at the site, which indicated that the station is in clouds approximately 40 % of the time throughout the year (Baltensperger et al, 1998).…”
Section: Instrumentation and Sitementioning
confidence: 99%
“…at the Jungfraujoch (JFJ) in the Swiss Alps at 7 • 59 2 E, 46 • 32 53 N. During the winter months it is located in the free troposphere without regular injections from the planetary boundary layer (Coen et al, 2007) and it is frequently surrounded by mixed-phase clouds. The intensive measurement period of the Cloud and Aerosol Characterization Experiment 6 (CLACE 6) took place from 17 February to 14 March 2007.…”
Section: Sphinx Laboratory At the Jungfraujochmentioning
confidence: 99%